THE EFFECT OF TILLAGE SYSTEM AND HERBICIDE ON SURFACE RUNOFF AND EROSION FOR CASSAVA CROP FIELD IN LABORATORIUM LAPANG TERPADU OF AGRICULTURE FACULTY UNIVERSITY OF LAMPUNG - M Khory Andreawan (The University of Lampung, 2015)
Land degradationis amajor factor indecreasing the productivity of the land. Themostfrequently land degradationoccurred is due to surface runoff and erosion. One of the causes of the surface runoff and erosion is humantreatment.Human treatment of the land can accelerate or reduce surface runoff and erosion. This study aims todetermine the effect of both tillage systems and herbicide on surface runoff and erosion on crop cassava field inlaboratoriumlapang terpaduAgriculture Faculty,University ofLampung.The experimentwas designas a factorialin randomized complete block design with four block. This experiment used multislot devicermethod with size 4x 4meter. Treatment consists of two factorswhich are tillage systemand herbicide. The results of this experimentindicate that tillage system did not affect surface runoff and erosion significantly and herbicide treatmentincrease surface runoff compare to treatment without herbicide, which is 32,8 mm and 24,6 mm, but did notsignificantly affect erosion.Keywords: Tillage,Herbicide,Run off, Erosion